Spatial distribution, sources, ecological risk assessment of heavy metals in surface sediments of Wular lake, Kashmir, India-a Ramsar site - Nazir, Arfat; Riyaz, Muzafar; Zargar, Mohammad Abass; Afzal, Mohamed (Frontiers in Environmental Science, 2025)
IntroductionWular Lake, one of the largest freshwater lakes in South Asia and a Ramsar-designated site, sustains biodiversity, fisheries, and livelihoods in the Kashmir Valley. However, increasing anthropogenic activities have raised concerns about heavy metal (HM) contamination in its sediments due to their persistence and ecological risks.MethodsA total of 32 surface sediment samples were collected from Wular Lake to determine the levels, distribution, and potential sources of HMs including Co, Cu, Fe, Mn, Ni, Pb, Zn, and Cr. Grain size composition, concentration analysis, and pollution indices such as contamination factor (CF), geoaccumulation index (Igeo), enrichment factor (EF), pollution load index (PLI), and potential ecological risk index (PERI) were applied. Multivariate statistics, including correlation, factor, and cluster analyses, were used to identify pollution sources.ResultsSediments predominantly comprised silt (5.8%–88.8%). Average HM concentrations were Co (34.26 mg/kg), Cu (53.2 mg/kg), Mn (1,478 mg/kg), Ni (78.85 mg/kg), Zn (113 mg/kg), and Cr (96.08 mg/kg), all exceeding natural background levels, suggesting anthropogenic enrichment. Risk assessment indicated moderate contamination (PLI = 1.17; PERI = 19.20), with site-specific hotspots of elevated pollution. Strong correlations were observed among Co, Ni, Fe and among Cu, Pb, Zn. Factor analysis attributed 77.1% of the variance to industrial, urban, and agricultural activities, while cluster analysis segregated sites according to pollution intensity.DiscussionThe findings indicate that Wular Lake sediments are moderately contaminated by heavy metals, primarily due to industrial discharge, agricultural practices, and urban runoff. Although the overall ecological risk was low to moderate, localized hotspots warrant urgent monitoring and management. Strengthening pollution mitigation measures is essential to safeguard the ecological health of this Ramsar site.